Pengaruh Kepemimpinan Transformasional Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Badan Perencanaan Pembangunan Daerah Kabupaten Tulungagung - nurhamdiah christianingrum (Otonomi, 2020)
Leadership is a process of influence in determining organizational goals, motivating followers' behavior to achieve goals, influencing to improve the group and its culture. This study aims to: (1) Analyze the effect of transformational leadership and work motivation simultaneously on employee performance at the Tulungagung Regional Development Planning Board. (2) Analyze the effect of transformational leadership partially on employee performance in the Regional Development Planning Board of Tulungagung Regency. (3) Analyze the effect of work motivation partially on employee performance in the Regional Development Planning Board of Tulungagung Regency. (4) Analyze transformational leadership variables and which work motivation variables are most dominant on employee performance at the Tulungagung Regional Development Planning Agency. This study uses a quantitative analysis method which is an analysis used on data in the form of numbers. Whereas technical data analysis uses: 1) validity and reliability test, (2) classic assumption-normality test, and (3) multiple regression assumption test. The results showed that: (1) The effect of transformational leadership and work motivation simultaneously had a significant effect on employee performance at the Tulungagung Regional Development Planning Agency. (2) The effect of individual transformational leadership has a significant effect on employee performance partially at the Regional Development Planning Agency of Tulungagung Regency. (3) The effect of work motivation partially has a significant effect on employee performance in the Regional Development Planning Board of Tulungagung Regency. (4) Transformational leadership variables have the most dominant influence on employee performance at the Regional Development Planning Agency of Tulungagung Regency.